The Undergraduate Students' Difficulties in Writing Thesis Proposal - Fauzan, Umar; Hasanah, Nur; Hadijah, Siti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
The purposes of this research were to find out the students’ difficulties in developing a paragraph and to understand the students’ difficulties in implementing the writing elements in writing their undergraduate thesis proposals. This research used the descriptive qualitative method. The instrument used in this research were interviews, documentation, and Oshima & Hogue’s Paragraph Rubric. The research subject was 7 eighth-semester students of UINSI Samarinda. The data were collected from the background of the study of the student’s undergraduate thesis proposals and analyzed with the Miles and Huberman Model. The result showed that the difficulties in developing a paragraph experienced by the students were related to too specific and too general topic sentences, poor supporting sentences, the absence of concluding sentences, inconsistent topic discussion, and inharmonic sentences. At the same time, the students’ difficulties shown in implementing the writing elements were found in the organization (the failure to run the sentences smoothly), vocabulary (informal phrases, redundancy, unclear word), grammar (singular and plural error, wrong word choice errors, missing word error, article error, subject-verb agreement error, fragment error, conjunction error, wrong word form error, wrong word order error, and preposition error), and mechanics (capitalization error, punctuation error, and spelling error). The causes of these problems were the interference of students’ native language and the lack of knowledge about the rules of the development of paragraph and writing elements.